**Exercise 1.3**

**1. Find the value of 36 ÷ 6 + 3.**

**Solution:**

36 ÷ 6 + 3 = 6 + 3

= 9

**2. Find the value of 24 + 15 ÷ 3.**

**Solution:**

24 + 15 ÷ 3 = 24 + 5

= 29

**3. Find the value of 120 – 20 ÷ 4.**

**Solution:**

120 – 20 ÷ 4 = 120 – 5

= 115

**4. Find the value of 32 – (3 × 5) + 4.**

**Solution:**

32 – (3 x 5) + 4 = 32 – 15 + 4

= 17 + 4

= 21

**5. Find the value of 3 – (5 – 6 ÷ 3).**

**Solution:**

3 – (5 – 6 ÷ 3) = 3 – (5 – 2)

= 3 – 3

= 0

**6. Find the value of 21 – 12 ÷ 3 × 2.**

**Solution:**

21 – 12 ÷ 3 × 2 = 21 – 123 × 2

= 21 – 4 × 2

= 21 – 8

= 13

**7. Find the value of 16 + 8 ÷ 4 – 2 × 3.**

**Solution:**

16 + 8 ÷ 4 – 2 × 3

= 16 + 2 – 6

= 18 – 6

= 12

∴ 16 + 8 ÷ 4 – 2 × 3 = 12

**8. Find the value of 28 – 5 × 6 + 2.**

**Solution:**

28 – 5 × 6 + 2 = 28 – (5 × 6) + 2

= 28 – 30 + 2

= 30 – 30

= 0

**9. Find the value of (-20) × (-1) + (-28) ÷ 7.**

**Solution:**

(-20) × (-1) + (-28) ÷ 7 = 20 + ∣-28∣ ∣7∣

= 20 – 287

= 20 – 4

= 16

**10. Find the value of (-2) + (-8) ÷ (- 4).**

**Solution:**

(-2) + (-8) ÷ (- 4) = – 2 + ∣- 8∣ ∣- 4∣

= – 2 + 2

= 0

**11. Find the value of (- 15) + 4 ÷ (5 – 3).**

**Solution:**

-15 + 4 ÷ (5 – 3) = – 15 + 4 ÷ 2

= – 15 + 2

= – 13

-15 + 4 ÷ (5 – 3) = – 13

**12. Find the value of (- 40) × (-1) + (-28) ÷ 7.**

**Solution:**

(- 40) × (-1) + (-28) ÷ 7 = 40 + (- 4)

= 40 – 4

= 36

**13. Find the value of (-3) + (-8) ÷ (-4) – 2× (-2).**

**Solution:**

(-3) + (-8) ÷ (-4) – 2 × (-2) = (-3) + (-8)(-4) – 2×(-2)

= – 3 + 2 + 4

= 6 – 3

= 3

**14. Find the value of (-3) × (-4) ÷ (-2) + (-1).**

**Solution:**

(-3) × (-4) ÷ (-2) + (-1) = 12 ÷ (-2) + (-1)

= – 6 – 1

= – 7

∴ (-3) × (-4) ÷ (-2) + (-1) = – 7